The social impact of computers - Rosenberg, Richard S. (San Diego, Calif. Academic Press, 1997)
This text reflects recent trends and ways of thinking about computerization and social issues with special emphasis on the Internet. It includes background information on computers, and covers computer applications in areas such as business and medicine, and their social implications.
Includes bibliographical references and index.
Keywords: Computers -- Social aspects